VP2 of Infectious Bursal Disease Virus Induces Apoptosis via Triggering Oral Cancer Overexpressed 1 (ORAOV1) Protein Degradation - Qin, Yao; Xu, Zhichao; Wang, Yongqiang; Li, Xiaoqi; Cao, Hong; Zheng, Shijun J. (Frontiers in Microbiology, 2017)
Infectious bursal disease (IBD) is an acute, highly contagious and immunosuppressive avian disease caused by IBD virus (IBDV). Cell apoptosis triggered by IBD virus (IBDV) contributes to the dysfunction of immune system in host. VP2 of IBDV is known to induce cell death but the underlying mechanism remains unclear. Here we demonstrate that VP2 interacts with the oral cancer overexpressed 1 (ORAOV1), a potential oncoprotein. Infection by IBDV or ectopic expression of VP2 causes a reduction of cellular ORAOV1 and induction of apoptosis, so does knockdown of ORAOV1. In contrast, over-expression of ORAOV1 leads to the inhibition of VP2- or IBDV-induced apoptosis, accompanied with the decreased viral release (p<0.05). Thus, VP2-induced apoptosis during IBDV infection is mediated by interacting with and reducing ORAOV1, a protein that appears to act as an antiapoptotic molecule and restricts viral release early during IBDV infection.